Development of Pharmaceutical Equivalent Montelukast Sodium Immediate-Release, Film-Coated Tablets - Muenraya, Poowadon; Atipairin, Apichart; Srichana, Teerapol; Changsan, Narumon; Balekar, Neelam; Sawatdee, Somchai (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Montelukast tablets are sold under the brand name Singulair and are used to control and prevent asthma symptoms. In this study, 10 mg film-coated montelukast tablets were developed as a generic drug in order to evaluate the pharmaceutical equivalent of the innovator’s products. The primary formulation ingredients used in all developed formulations (F1-F5) were the same as those described in the Singulair tablet package insert, except for formulations F3, F4, and F5, to which solubilizing enhancers were added to increase montelukast solubility. The core tablets were produced using the wet granulation method before being coated with HPMC polymer. FT-IR and DSC were used to determine drug and excipient compatibility. The micromeritic properties of the granules were assessed. The physicochemical properties of generated montelukast tablets and Singulair tablets were also investigated. The dissolution profiles of the tested drug and the innovator were assessed in a variety of pH mediums (pH 1.2, 4.5, 6.8, and water). The similarity (f2) and difference (f1) factors were computed. The accelerated and long-term stability of the tested drug in hot and humid climate zones was evaluated. The analytical method validation used in this study was ICH-acceptable for 8 parameters including specificity, range, linearity, accuracy, precision, limit of detection, limit of quantitation, and robustness. F1-F5 granules had similar properties, such as a pale-yellow color and excellent flow properties. There were no chemical interactions between montelukast and the excipients according to FT-IR and DSC analyses. The physical properties of all developed montelukast film-coated tablets were similar (average weight 212-218 mg; thickness 3.02-3.07 mm; assay 101-102% LA; disintegration time 3-4 min), except that the disintegration time of F3 was 8.10 min and that of F5 was 5.90 min, which was caused by the addition of poloxamer 188 to the formulation. In all mediums, only the F1 formula produced acceptable comparison dissolution profiles to Singulair. After 6 months of storage under accelerated and long-term conditions, the results showed the F1 formulation remained physically and chemically stable.